Subjects with fibromyalgia syndrome have a reduction of balance performance - Vaillant, Jacques; Pissety, Sophie; Martinez, Silvia; Juvin, Robert (Annals of physical and rehabilitation medicine, 2016)
If subjects with fibromyalgia syndrome (FMS) firstly describe painful and fatigue syndromes, secondly some of them described latent postural disorders or frailty. If decrease of postural performance has been described on osteoarthritis diseases of lower limb, it is unknown on fibromyalgia. The aim of this study was to assess clinical perform on balance and gait of patients with FMS. The sample was selected in-patients or in consultation in the rheumatology department and from those patients participating in a programme of rehabilitation. The balance of these patients was investigated by the use of four clinical tests usually employed: Timed Up and Go test (TUG), One Leg Balance (OLB), Berg Balance Scale (BBS) and Lateral Reach Test (LRT). The OLB was conducted in two conditions: (1) with open eyes, (2) with eyes closed. Finally, the sample included 31 patients (average age 47±5.6 years), with 29 women. Twenty-three subjects already had dizziness against 6 subjects who have never felt dizzy. Eighteen subjects have already fallen once or more. Twenty-five have drug treatment acting directly or indirectly on their balance. OLB was 38.87±31.5s [28.32; 5.88–120.00] (Mean±SD [median; min–max]) with open eyes and 8.00±6.8s [5.05; 2.02–34.99] with eyes closed condition. The Timed Up and Go test score was 11.15±3.08s [11.57; 6.13–18.98]. The LRT was 15.6±6.9cm [14.4; 3.1–27.6]. The BBS was 48±6 [50; 37–56]. According to the definitions of postural perform references, the results showed deficit of balance and locomotion among patients with FMS. Analytic clinical tests (OLB and LRT) show reduced ability compared to age based norms. For OLB with open eyes, Ekdahl et al. (1989) considered, 60s as standard perform. For LRT, Brauer et al. (1999) indicated standard perform is 20±2cm. We noted similar results for the functional tests such as the BBS and TUG. The patients with FMS demonstrated balance impairments. Balance and gait analysis could be proposed as an objective measurement and treatment to assess the impact of rehabilitation in FM. Further studies are needed in order to take into account the effect of FM heterogeneity.